2021
DOI: 10.1002/ab.21988
|View full text |Cite
|
Sign up to set email alerts
|

The effect of classroom aggression‐related peer group norms on students' short‐term trajectories of aggression

Abstract: Using a four-wave/seven-month longitudinal design with a sample of 1595 preadolescents (53% boys, 47% girls, M age = 10.2 years) from 63 fourth-, fifth-and sixth-grade classrooms in nine mixed-sex schools in Bogotá, Colombia, we examined whether growth trajectories of measures of overt and relational aggression varied as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…A social network study found that friendship selection and influence processes related to aggression depended on the popularity norm rather than the descriptive classroom norm (Laninga-Wijnen et al, 2017). Other research found that popularity norms (especially prevalence-based rather than correlation-based popularity norms) better predicted overt and relational aggression trajectory membership than did perceived prescriptive norms (Velásquez et al, 2021), and that classroom popularity norms for aggression moderated the relation of overt and relational aggression with social preference (peer likeability) more strongly than did classroom descriptive norms (Jackson et al, 2015). More insight is needed into what operationalization of norms is best in predicting individual students' behaviors, as this would allow us to pinpoint what type of intervention is required to adjust students' behaviors.…”
Section: Differential Effects Of Different Types Of Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…A social network study found that friendship selection and influence processes related to aggression depended on the popularity norm rather than the descriptive classroom norm (Laninga-Wijnen et al, 2017). Other research found that popularity norms (especially prevalence-based rather than correlation-based popularity norms) better predicted overt and relational aggression trajectory membership than did perceived prescriptive norms (Velásquez et al, 2021), and that classroom popularity norms for aggression moderated the relation of overt and relational aggression with social preference (peer likeability) more strongly than did classroom descriptive norms (Jackson et al, 2015). More insight is needed into what operationalization of norms is best in predicting individual students' behaviors, as this would allow us to pinpoint what type of intervention is required to adjust students' behaviors.…”
Section: Differential Effects Of Different Types Of Normsmentioning
confidence: 99%
“…Popularity classroom norms are typically operationalized as the within-classroom correlation between a particular behavior and perceived popularity (e.g., Garandeau et al, 2022; Rambaran et al, 2022). An alternative for the correlation-based popularity norm is a prevalence-based popularity norm, where the average behavior of popular classmates is computed (Dijkstra et al, 2008; Menesini et al, 2015; Velásquez et al, 2021), or a network-based weighted norm, referring to a measure that gives more weight to the behavioral scores of students who hold a central position in the classroom network, based on the number of direct and indirect relationships (Jackson et al, 2015).…”
Section: Different Types Of Classroom Normsmentioning
confidence: 99%
“…What appears to matter most, at least for one's status in the classroom, is conforming to the prevailing behavioral norms. Our findings are consistent with previous research showing that children benefit socially when their behavior fits with what is normative in the classroom (e.g., Jackson et al, 2015, Velásquez et al, 2021 and that not conforming to prevailing norms has negative consequences such as exclusion and rejection (e.g., Juvonen & Galvan, 2008). Our findings are thus consistent with a normative social influence model (Cialdini & Goldstein, 2004) or a social context model (Chang, 2004).…”
Section: The Interplay Between Peer Contexts and Status (Aims 4 And 5)supporting
confidence: 92%
“…Studies have operationalized these norms in different ways. For example, in a previous study we examined the differential effects of different types of norms compared two measurement methods of classroom popularity norms: (a) the within-classroom correlation between popularity and aggression (correlation-based norm); and (b) the average level of aggression of the most popular children in each classroom (prevalence-based norm; Velásquez et al, 2021). Findings revealed that prevalence-based norms produced stronger effects compared with correlation-based norms.…”
Section: Classroom Popularity Normsmentioning
confidence: 99%